Genome-Wide Association Study of Nicotine Dependence in American Populations: Identification of Novel Risk Loci in Both African-Americans and European-Americans - Gelernter, Joel (Biol Psychiatry, 2014)
BACKGROUND: We report a genome-wide association study (GWAS) of nicotine dependence defined on the basis of scores on the Fagerström Test for Nicotine Dependence in European-American (EA) and African-American (AA) populations. METHODS: Our sample, from the one used in our previous GWAS, included only subjects who had smoked >100 cigarettes lifetime (2114 EA and 2602 AA subjects) and an additional 927 AA and 2003 EA subjects from the Study of Addiction: Genetics and Environment project [via the database of Genotypes and Phenotypes (dbGAP)]. GWAS analysis considered Fagerström Test for Nicotine Dependence score as an ordinal trait, separately in each population and sample and by combining the results in meta-analysis. We also conducted analyses that were adjusted for other substance use disorder criteria in a single nucleotide polymorphism (SNP) subset. RESULTS: In EAs, one chromosome 7 intergenic region was genome-wide significant (GWS): rs13225753, p = 3.48 × 10(−8) (adjusted). In AAs, GWS associations were observed at numerous SNPs mapped to a region on chromosome 14 of >305,000 base pairs (minimal p = 4.74 × 10(−10)). Two chromosome 8 regions were associated: p = 4.45 × 10(−8) at DLC1 SNP rs289519 (unadjusted) and p = 1.10 × 10(−9) at rs6996964 (adjusted for other substances), located between CSGALNACT1 and INTS10. No GWS associations were observed at the chromosome 15 nicotinic receptor gene cluster (CHRNA5-CHRNA3-CHRNB4) previously associated with nicotine dependence and smoking quantity traits. TSNAX-DISC1 SNP rs821722 (p = 1.46 × 10(−7)) was the most significant result with substantial contributions from both populations; we previously identified DISC1 associations with opioid dependence. Pathway analysis identified association with nitric oxide synthase and adenosine monophosphate-activated protein kinase pathways in EAs. CONCLUSIONS: The key risk loci identified, which require replication, offer novel insights into nicotine dependence biology.